From Trust Convergence to Trust Divergence: Trust Development in Conflictual Interorganizational Relationships - Brattström, Anna; Faems, Dries; Mähring, Magnus (Organization studies, 2019)
Whereas extant research on trust in interorganizational relationships tends to focus on trust convergence – i.e. members of one focal firm developing similar trust perceptions toward a partner firm – we shift focus to trust divergence – i.e. members of one focal firm developing different trust perceptions toward a partner firm. To explore trust divergence, we conduct an inductive, longitudinal study of one interorganizational relationship characterized by mutual transgressions. We identify shifts in attentional perspectives and referent categorizations as two novel mechanisms for theorizing trust development in interorganizational relationships. In particular, we develop a process model illuminating how these two mechanisms can contribute to trust development patterns in interorganizational relationships that are more discontinuous than existing models would predict. Moreover, we highlight the constructive implications of trust divergence for interorganizational collaboration in the presence of transgression and conflict.